Effects of birth month on talent identification participation and the identification process in sports - Kubo, J.; Nishikawa, S.; Morioka, Y.; Arikawa, H.; Tamaki, K. (Topics in Exercise Science and Kinesiology, 2021)
The purpose of this study was to clarify the effect of the birth month on Talent Identification (TI) participation and the identification process in sports. The subjects were 4th grade elementary school children (mean age, 9±5.8 years) who participated in the Talent Identification Project. The method of identification was two-stage. In the first stage, the 30 m sprint, standing broad jump, and medicine ball front throw (1 kg) were performed, and 99 boys and 97 girls with high overall scores were selected to participate in the second stage. In the second stage, in addition to the results of the first stage, the T-test, 20 m shuttle run, standing triple jump, rebound jump (RJ-index), medicine ball back throw (1 kg), and repeated horizontal jump were performed. In the T-test, subjects run straight to a point 10 m ahead, then, ran 5 m to the right, 10 m to the left, 5 m to the right, and returned 10 m back to the start. A total of 15 boys and 15 girls with high overall scores were selected from the second stage. As in a previous study, the birth month was divided into yearly quarters (1, April to June; 2, July to September; 3, October to December; and 4, January to March). Point of application #1: There was a bias in participation rates and final members in the TI project for 4th graders by birth month for both boys and girls. Point of application #2: In the case of 4th grade boys of the TI project, the medicine ball front throw, as an index of whole body power, was influenced by the birth month. Point of application #3: It was speculated that boys born between January and March had a smaller morphology (height and weight), and were disadvantaged in measurement tests related to morphology, such as the medicine ball front throw.